EFFECT OF LIME APPLICATION ON SOIL PROPERTIES AND SOYBEAN YIELD ON TIDAL LAND - Andy Wijanarko; Abdullah Taufiq (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
The problems of soybean cultivation on tidal land are low in soil fertility, aluminum (Al) toxicity and poor availability of macro nutrients. Soil acidity and Al toxicity are often fixed by liming. The research aimed to determine the calculation method of lime requirement and its application method for soybean on tidal land. The research was conducted on tidal land in South Kalimantan, Indonesia. Treatment consisted of two factors and arranged in randomize complete block design, replicated three times. The first factor was the method of lime rate calculation: (1) no liming,(2) liming based on10% of Al saturation, (3) liming based on 20% of Al saturation, (4) liming based on 30% of Al saturation, (5) liming based on 0.5 x exchangeable Al, and (6) liming based on 1 x exchangeable Al. The second factor was the method of application: (1) surface,and (2) mixed within 20 cm soil depth. The results showed that liming by mixing dolomite with soil within 20 cm depth resulted in 8% higher plant height compared to that applied on the soil surface. The highest yield was obtained when liming at rate equivalent to 10% of Al saturation was mixed with soil within 20 cm depth.